The influence of environmental factors on the pigment content in epiphytic moss species in the Caucasian Mineral Waters Area (Stavropol Territory) - A. F. Meysurova (Юг России: экология, развитие)
Aim. The impact assessment of ecological factors on the pigment content in mosses collected in the Caucasian Mineral Waters Area. The material studied consisted of epiphytic mosses (Anomodon viticulosus (Hedw.) Hook. & Taylor), Leucodon sciuroides (Hedw.) Schwägr.) collected from two mountainous locations – Mount Zheleznaya and Mount Beshtau. The pigment analysis was conducted at the laboratory of the Shared Facility Centre of Tver State University using generally accepted methodology in 2023.Changes in the light spectrum in high mountain conditions lead to an increase in the total pigment content due to the increase in Сhl b, which effectively absorbs short‐wave intense rays and a simultaneous decrease in Сhl a. The horizontal gradient of pigment concentration variation in mosses depends on the exposure of slopes, their steepness, plant type and other biotopic conditions.The study revealed the unique responses of mosses to local ecological factors, making them potentially valuable biomarkers of ecological changes.